The The Role of Reading Corner on The Effectiveness of Students' Reading Interest - Hadziq Fikri, Arief; Pratama, Anistya; Zulaikah, Zulaikah (English Education Program, Education Faculty, Universitas Nurul Huda, 2025)
The function of reading corners in boosting pupils' interest in reading is covered in this article. Students in the fourth grade served as the research subjects for this study, which was carried out in an elementary school. Data is gathered using interviews and observation in this qualitative descriptive method. Students' interest in reading is much increased when reading corners are implemented, according to the study's findings. Students' reading time intensity increases as a result of feeling content and at ease when participating in reading activities. An aesthetically pleasing reading nook with a diverse selection of books can foster an environment that encourages literacy-related activities. In order to establish an atmosphere that fosters students' enthusiasm in reading, this study highlights the significance of assistance from a variety of sources, including parents and instructors. The purpose of this article is to ascertain the relationship between literacy and sixth-grade students' reading comprehension at SDN 04 Banding Agung. This study employs a qualitative methodology that includes a descriptive qualitative approach and techniques for gathering data, such as documentation and observation. The findings of the study indicate that: (1) students' interest in reading is significantly influenced by the reading corner; (2) having a reading corner in the classroom facilitates students' access to reading materials from within the classroom; and (3) students would rather read books in the reading corner than in the library.In order to assist students grasp the content more thoroughly and to improve teaching standards in schools, this study makes recommendations for a curriculum that places a greater emphasis on enhancing literacy and students' enthusiasm in reading in the classroom.